Hospital Waste Management (International Journal of Innovative Research in Engineering & Management, 2021)
Healthcare activities can result in a variety of hazardous waste.  Mismanagement may have a negative impact on the  environment and pose a health risk in the workplace.  Developed countries have limited financing when it comes to  the safe disposal of medical waste. The major problems in the  management of hospital waste in industrialized nations are  summarized in this paper. An examination of the current  situation literature reveals that numerous earlier  accomplishments in laws and regulations aimed at patient care  have squandered these countries. Those are the nations. These  regulations differ from one hospital to the next. In contrast,  there are significant variations in trash generation trends inside  and surrounding these countries. This is due in part to a lack of  a common description and the researchers' techniques for  quantifying waste. In comparison, hospitals in these nations are  lacking in terms of waste separation, collection, processing,  transportation, and treatment, posing occupational and  environmental risks. Clinic staff' knowledge and  comprehension of effective waste management are restricted  due to a lack of training. Hospital waste disposal in  industrialized countries is plagued by a slew of issues. It is  possible to decrease the negative effects of hospital wastes by  engaging in sustainable waste management operations.
Keywords: Clinical Waste; Infectious waste; Hospital waste; Hospital Management; Sustainable Development